Media, Power and Heritage Policy: A Critical Discourse Analysis of Himeji Castle’s Entry Fee Proposal - Fitri Ifi Gama; I Nyoman Sudiana (Soegijapranata Catholic University, 2025)
This research aims to critically analyze a news article discussing the Mayor of Himeji's proposal to increase entry fees for foreign tourists visiting Himeji Castle using Norman Fairclough's Critical Discourse Analysis (CDA) model. The study's significance lies in understanding how media discourse shapes public perception and policy decisions regarding tourism and heritage preservation. The methodology involves three levels of analysis: textual, discursive practice, and social practice. The results indicate that the media plays a crucial role in framing policy debates and influencing public opinion. The textual analysis reveals strategic language choices that frame the fee increase as a necessary measure for sustainable tourism and heritage preservation. Discursive practice analysis shows how the article's production context and use of authoritative quotes lend credibility to the policy while highlighting a bias by omitting diverse perspectives. The social practice analysis situates the discourse within broader socio-economic and political contexts, emphasizing the tension between economic benefits and cultural preservation. The study underscores the need for sustainable tourism practices that balance local and global interests and contribute to preserving cultural heritage sites